Human–Wildlife Conflict Dynamics and Conservation Challenges in Gullele Botanic Garden, Ethiopia - Yihew B. Woldegiorgis; Mekbib M. Yimberber; Zelalem T. Assaye (International Journal of Zoology)
Human–wildlife conflict (HWC) commonly arises in areas where human settlements and wildlife habitats intersect, particularly around the border of conservation zones. This study assessed the status of HWC, in Gullele Botanic Garden (GBG), Ethiopia. We conducted 120 questionnaire interviews with selected employees of the garden; moreover, focus group discussions, key informant interviews, and observations were also used during data collection. Nearly 70% of the respondents confirmed the existence of severe HWC in the garden. Statistically significant variation was recorded among respondents about severity (χ2 = 14.79, df = 2, and p≤0.05) of the conflict. Our findings indicated that most of the conflicts occurred at night (75.8%) and during the dry season (40%). Warthog (25%), porcupine (20%), and hyena (18%) were reported as the top three wild animals involved in HWC. Feeding on planted seedlings (38.6%), damage to prepared seedlings in the nursery sites (21.7%), and destruction to infrastructure (18.1%) were the three principal causes of the conflict. A total of 26,406 USD per annum is lost due to HWC. Awareness creation campaigns, construction of nature-based live fences, and application of mechanical rodent management technologies should be applied as HWC mitigation strategies in the garden.